Influence of phase composition on microstructure and thermal properties of ytterbium silicate coatings deposited by atmospheric plasma spray. Issue 11 (September 2018) - Zhu, Tao; Niu, Yaran; Zhong, Xin; Zhao, Jun; Zeng, Yi; Zheng, Xuebin; Ding, Chuanxian
Abstract: In this study, ytterbium silicate coatings with different compositions were designed by controlling the Yb2 O3 / SiO2 ratio and fabricated by atmospheric plasma spray. The microstructure and thermal properties of these coatings were characterized. Results showed that the Yb2 O3 -rich coatings contained Yb2 O3 and Yb2 SiO5 phases, which were characterized by Yb2 O3 columnar grains, obvious interfaces between splats and many microcracks. The SiO2 -rich coatings were composed of Yb2 SiO5 and Yb2 Si2 O7 phases, which were composed of well bonded splats with many spherical pores. The Yb2 O3 -rich coatings had higher coefficient of thermal expansion values and lower thermal conductivities than the SiO2 -rich coatings. The SiO2 -rich coatings presented much better thermal cycling resistance than the Yb2 O3 -rich coatings. The relationship among phase composition, microstructure and thermal properties of ytterbium silicate coatings was analyzed. The results of this study may provide some clues for designs and applications of rare-earth silicates as environmental barrier coatings.